2005
DOI: 10.1177/1420326x05054069
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Environmental Tobacco Smoke to Indoor Pollution in Pubs and Bars

Abstract: Smoking is currently allowed in most UK pubs and bars and smoking policies are self regulated by the hospitality industry through the Public Places Charter, which encourages the provision of non-smoking areas and improved ventilation. In this study monitoring of environmental tobacco smoke (ETS) has been conducted in 60 pubs and bars in the Greater Manchester area to determine the effectiveness of different smoking policies. The ETS markers RSP (as PM2.5), UVPM, FPM, SolPM and nicotine were sampled at several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Gee et al 4 reported on measurements carried out in 60 public houses in Manchester, UK. Again a range of markers were reported, respirable suspended particulates, (PM2.5), ultraviolet particulate matter, fluorescent particulate matter, solanesol particulate matter, and vapour phase nicotine.…”
Section: The Decay Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gee et al 4 reported on measurements carried out in 60 public houses in Manchester, UK. Again a range of markers were reported, respirable suspended particulates, (PM2.5), ultraviolet particulate matter, fluorescent particulate matter, solanesol particulate matter, and vapour phase nicotine.…”
Section: The Decay Equationmentioning
confidence: 99%
“…Attention has been focused on the issue of smoking in public places following the introduction of a smoking ban in pubs in Ireland in 2004 1 and the 2006 'yes' vote by the House of Commons to introduce a smoking ban in the summer of 2007. 2 Concerns raised by laboratory tests and field studies concluding that ventilation systems were ineffective in reducing levels of environmental tobacco smoke (ETS), 3,4 would have been used in lobbying for the 'yes' vote. In campaigning for these bans organizations such as ASH have presented ventilation in a very poor light.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the scientific evidence relating to this debate has been reported in a diverse range of publications such as the British Medical Journal (BMJ), Indoor Air and the Chartered Institute of Building Services Engineers (CIBSE) Journal. On inspection much of this reporting concludes negatively on the performance of ventilation systems (Mulcahy, Repace 2000;Carrington et al 2002Carrington et al , 2003Gee et al 2005Gee et al , 2006Kotzias et al 2004).…”
Section: Introductionmentioning
confidence: 94%
“…In recent years, several European countries (Ireland, Norway, Italy, Malta, Sweden, Spain, Finland, Scotland, Belgium, France and UK) have issued smoking policy rules in indoor workplaces and/or hospitality premises, including restaurants, to protect non-smoking people from environmental tobacco smoke (ETS) and consumption of tobacco products, with a good compliance [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%